2020
DOI: 10.1111/jmwh.13085
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcal Bacteriuria in Pregnancy: An Evidence‐Based, Patient‐Centered Approach to Care

Abstract: Screening and management of group B streptococcus (GBS) bacteriuria in pregnancy aims to reduce the incidence of pyelonephritis and GBS‐related neonatal morbidity and mortality. Universal screening and management of GBS bacteriuria in pregnancy are standards of care in the United States; however, some women may decline guideline‐based recommendations for screening, treatment, or intrapartum antibiotic prophylaxis. This article uses a case study approach to discuss evidence‐based, patient‐centered care for GBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There are some serious risks associated with giving antibiotics to pregnant women, so there are a number of rules to follow determined by the condition of the patients, the type of examinations and procedures performed and the mode of delivery [1,2,4,5]. Antibiotics with the lowest possible risk of adverse effects should be chosen, which often means choosing older antibiotics with documented safety in pregnancy [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are some serious risks associated with giving antibiotics to pregnant women, so there are a number of rules to follow determined by the condition of the patients, the type of examinations and procedures performed and the mode of delivery [1,2,4,5]. Antibiotics with the lowest possible risk of adverse effects should be chosen, which often means choosing older antibiotics with documented safety in pregnancy [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…When considering other antimicrobial therapies in pregnancy, such as the treatment of asymptomatic bacteriuria or bacterial vaginosis (BV), and the overuse of antibiotics to treat respiratory and genital tract infections, it is reasonable to assume that the vast majority of fetuses are now exposed to antibiotics before birth [1][2][3]. The following antibiotics may be used during pregnancy: penicillins (amoxicillin and ampicillin), cephalosporins (cefazolin, cephalexin, ceftriaxone and cefuroxime), macrolides (erythromycin) and cotrimoxazole (contraindicated in the first trimester of pregnancy) [2,4,5]. According to the Polish recommendations, all women undergoing an elective or emergency caesarean section should receive antibiotic prophylaxis, and a single dose of first-generation cephalosporins is the drug of choice [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GBS colonisation of the urinary tract during pregnancy can represent heavy maternal colonisation, with increased risks of preterm labour, pyelonephritis and low birth weight, however recent research has found GBS bacteriuria in pregnancy to have low positive predictive values for vaginal colonisation at birth (Khalil, Thorsen, Møller, & Uldbjerg, 2018). A recent Cochrane review found the evidence for risks of GBS bacteriuria to be of low quality, and called for research to conduct risk: benefit analyses, including cost-benefit, long term outcomes including the neonatal microbiome, particularly in low-risk women (Schafer & Phillippi, 2020;Smaill & Vazquez, 2019).…”
Section: Antenatal Carementioning
confidence: 99%